Pengaruh Pemberian Endorphin Massage Terhadap Penurunan Dismenore Pada Remaja Putri di SMP Negeri 1 Kotaagung Barat - Nia Erviza; Rina Sri Widayati (Pusat Riset dan Inovasi Nasional, 2024)
Background: dysmenorrhea refers to pain, tenderness and cramps felt in the lower abdomen during menstruation which can interfere with daily activities. In Indonesia alone, dysmenorrhea reached 107,673 people (64.25%). One way to relieve dysmenorrhea is with endorphin massage. This massage stimulates the release of endorphins which act as morphine (pain reliever). Objective: To determine the effect of giving endorphin massage on reducing dysmenorrhea pain in adolescent girls at SMP Negeri 1 Kotaagung Barat. Research method: the type of research used was pre-experimental with a one group pre-test post-test design with a sample size of 20 people. Results: shows the p-value before and after giving endorphin massage of 0.000<0.05. Conclusion: There is an effect of giving endorphin massage on reducing dysmenorrhea at SMP Negeri 1 Kotaagung Barat.